Konsep Sistem Gadai Emas dan Penerapannya di Bank Syariah Indonesia Kantor Cabang Pembantu Gunung Tua - Bona Darwisah Pohan; Khairina Tambunan (Medan Resource Center, 2021)
This study examines the implementation of the Islamic gold pawn (rahn) system at Bank Syariah Indonesia Kantor Cabang Pembantu Gunung Tua within the context of Indonesia’s dual sharia pawn framework, where Islamic pawnshops and Islamic banks serve different collateral and financing roles. The research problem addresses how gold-based rahn is operationalized in Islamic banking and whether its practices comply with Sharia principles. Using a qualitative approach, data were collected through observation, in-depth interviews, and documentation, supported by relevant literature. The findings indicate that the gold pawn system at this branch is structured through clear requirements, contract arrangements, valuation mechanisms, collateral maintenance, maturity and liquidation procedures, and multifunctional customer services. The implementation is continuously supervised by the National Sharia Council (DSN–MUI) and grounded in the Qur’an and Hadith. The study concludes that the gold pawn practices at Bank Syariah Indonesia KCP Gunung Tua conform to Islamic legal principles, reinforcing the view that all forms of muamalah are permissible unless explicitly prohibited by Sharia, thereby validating rahn as a legitimate and socially responsive Islamic financial instrument.